Emergency response of four transfusion centers during the last Chikungunya outbreak in Italy. Issue 12 (13th October 2018) - Pierelli, Luca; Vacca, Michele; Zini, Gina; Maresca, Maddalena; Menichella, Giacomo; Santinelli, Susanna; Stigliano, Maria Alba; Mandarello, Gabriele; Gasbarri, Roberto; Vaglio, Stefania
Abstract : Between September 15 and November 11, 2017, the area of Rome was subjected to cessation of donation in an area of approximately 1, 300, 000 inhabitants and with a 5‐day quarantine for the rest of metropolitan areas due to Chikungunya virus (CHIKV) outbreak. Quarantine was applied to red blood cell (RBC) and plasma units while platelet concentrates (PCs) were subjected to pathogen inactivation methods (PIMs). Quarantine was based on an active recall of all donors and, in case of declared absence of any symptom or illness, on release of RBC and plasma units after 5 days. Four regional centers in which PIMs were already performed were charged for PIMs for the rest of Rome's area. These centers increased by 236% their previous PIM procedures, producing additional 1425 pathogen‐reduced (PR) PCs in 57 days, beside their production (996 PR PCs) for local needs. The emergency support was close to the maximal production capacity of the four centers and was successful only thanks to the limited length of emergency. No adverse events were reported by all centers through a passive hemovigilance approach and by a follow‐up of approximately 4 months. None of the donors referred symptoms or illness at recall and none of the blood products were discarded after quarantine. To date, no cases of CHIKV‐transmitted infection were reported in transfused patients. This experience has taught some relevant strategic and organizing aspects that should be taken into account when an infectious outbreak must be faced in a large metropolitan area.